Effective Polysulfide Rejection by Dipole‐Aligned BaTiO3 Coated Separator in Lithium–Sulfur Batteries. (20th September 2016) - Yim, Taeeun; Han, Seung Ho; Park, Nam Hwan; Park, Min‐Sik; Lee, Ji Hoon; Shin, Jaeho; Choi, Jang Wook; Jung, Yongju; Jo, Yong Nam; Yu, Ji‐Sang; Kim, Ki Jae
Abstract : Although the exceptional theoretical specific capacity (1672 mAh g −1 ) of elemental sulfur makes lithium–sulfur (Li–S) batteries attractive for upcoming rechargeable battery applications (e.g., electrical vehicles, drones, unmanned aerial vehicles, etc.), insufficient cycle lives of Li–S cells leave a substantial gap before their wide penetration into commercial markets. Among the key features that affect the cyclability, the shuttling process involving polysulfides (PS) dissolution is most fatal. In an effort to suppress this chronic PS shuttling, herein, a separator coated with poled BaTiO3 or BTO particles is introduced. Permanent dipoles that are formed in the BTO particles upon the application of an electric field can effectively reject PS from passing through the separator via electrostatic repulsion, resulting in significantly improved cyclability, even when a simple mixture of elemental sulfur and conductive carbon is used as a sulfur cathode. The coating of BTO particles also considerably suppresses thermal shrinkage of the poly(ethylene) separator at high temperatures and thus enhances the safety of the cell adopting the given separator. The incorporation of poled particles can be universally applied to a wide range of rechargeable batteries (i.e., metal‐air batteries) that suffer from cross‐contamination of charged species between both electrodes. Abstract : Poling for polysulfide rejection: The fatal shuttling process in lithium–sulfur batteries is effectively suppressed by "poled" BaTiO3 or BTO particles coated on a poly(ethylene) separator. The permanent dipoles of poled BTO particles repel polysulfides via electrostatic repulsion. The coating of BTO particles also provides a resistance against thermal shrinkage of the polyethylene separator at high temperature, thus enhancing the safety of the given cell.